Synthesis of 4-alkylsulfanylphthalazin-1(2H)-ones via palladium catalyzed sulfanylation of substituted 4-bromophthalazin-1(2H)-ones. Issue 49 (8th December 2016) - Malinowski, Zbigniew; Fornal, Emilia; Sierocińska, Beata; Czeczko, Renata; Nowak, Monika
Abstract: The synthesis of a series of new alkylsulfanyl phthalazinone and phthalazine derivatives is described. The target compounds were efficiently synthesized in a four step sequence, consisting of (1) cyclization of 2-formylbenzoic acid with hydrazine hydrate to form phthalazinone, (2) the direct bromination of phthalazinone core with KBr3, (3) alkylation of the obtained 4-bromolactam (Mitsunobu procedure) to make N - and also O -alkyl derivatives and finally (4) palladium-catalyzed coupling reactions of 2-alkyl-4-bromophthalazinone and 1-alkyloxy-4-bromophthalazine derivatives with aliphatic mercaptanes. Furthermore, the synthesis of 2-methyl-8-(propan-2-yl)sulfanyl-pyrido[3, 4- d ]pyridazin-1(2 H )-one from 2-methyl-pyrido[3, 4- d ]pyridazin-1(2 H )-one via bromination reaction with KBr3 and subsequent sulfanylation by isopropyl mercaptan under catalyzed coupling reaction conditions is also described. Graphical abstract: